Calcareous nannofossil biostratigraphy, bioevents, and palaeoecological interpretation of the lower-middle Miocene outcrops in west central Sinai (Egypt) - Abu Shama, Aziz; El-Nahrawy, Sara; Farouk, Sherif; Jovane, Luigi; Al-Kahtany, Khaled; Zaky, Amr S. (Frontiers in Earth Science, 2024)
The Burdigalian/Langhian (B/L) boundary has not yet been designated as a Global Stratotype Section and Point (GSSP), despite various proposed zonal schemes. In the Gulf of Suez region of Egypt, the Burdigalian-Langhian successions are notable for hosting significant hydrocarbon reservoirs within a tectonic rift setting. Therefore, biostatigraphy plays a crucial role in exploration endeavors in this area. The nannofossil biostratigraphy is investigated in two sections, Wadi Baba and Wadi Gharandel, of the lower-middle Miocene from west-central Sinai. Three biozones, NN3 (Sphenolithus belemnos) Zone, NN4 (Helicosphaera ampliaperta) Zone, and NN5 (Sphenolithus heteromorphus) Zone, are identified from the studied interval. The NN4 Zone could be divided into MNN4a/b and MNN4c. Important biovents are discussed, such as the Sphenolithus heteromorphus paracme interval and the first occurrence and evolution of the Discoaster exilis and D. variabilis Calcareous Nannofossil Biostratigraphy, Bioevents, and Palaeoecological Interpretation of the Lower-Middle Miocene Outcrops in West Central Sinai (Egypt) 2 groups. Based on the cluster analysis, the recorded taxa can be subdivided into four groups that reflect their palaeoclimatic preferences. The paleoecological interpretation of the studied Rudies Formation indicates prevailing cool and eutrophic nutrient conditions based on the dominance of taxa such as Coccolithus pelagicus, Reticulofenestra minuta, and Cyclicargolithus floridanus. The nannofossil taxa responses to sea level curve are interpreted. Fluctuations in taxa abundance and diversity indicate a slight rise in the sea level at the base of the Burdigalian followed by sudden drop in the sea level at the middle Burdigalian. High sea-level conditions prevailed again until the B/L boundary. During the Langhian period, many small-scale fluctuations in sea-level curve are detected.